2015
DOI: 10.7844/kirr.2015.24.4.22
|View full text |Cite
|
Sign up to set email alerts
|

Formation Behavior of Precipitated Calcium Carbonate Polymorphs by Supersaturation

Abstract: 속도론적인 관점에서 실험변수를 조절하여 얻어진 결과로부터 침강성 탄산칼슘(precipitated calcium carbonate, PCC)의 생성을 핵 생성속도로 규명하였다. 반응온도 80 o C에서 Ca(OH) 2 slurry, Na 2 CO 3 수용액 및 다양한 농도의 NaOH를 첨가하여 침강성 탄산칼슘 의 생성거동을 관찰하였다. 핵생성속도는 주 반응물인 Ca 2+ 이온과 CO 3 2-용해속도를 조건으로 나누어 진행하였다. 두 이온의 농도 가 고농도일경우에는 vaterite와 calcite가 혼재되어 나타났다. Ca 2+ 이온과 CO 3 2-이온농도 중 어느 하나만을 낮게 하여 반응시킨 경 우에는 주로 calcite가 생성되었으며 두 이온농도가 모두 낮을 경우에는 aragonite가 형성되었다. 또한 NaOH 농도를 증가시킴에 따 라 calcite의 생성은 감소하였으며 5M NaOH 수용액 내에서 단일상의 aragonite를 얻을 수 있었다. 따라서 본 연구에서는 과포화도 조절을 통해 다형체(polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Here the excess of Mg may be less detrimental since there is less carbonate ions available for crystallization, hence the magnesium's role is limited to being a calcite poison rather than a magnesian-calcite building block. The level of supersaturation may also play a role here, as it has been shown that supersaturation control can influence the CaCO 3 polymorph formation (Ahn et al, 2015).…”
Section: Influence Of Reaction Volumementioning
confidence: 99%
“…Here the excess of Mg may be less detrimental since there is less carbonate ions available for crystallization, hence the magnesium's role is limited to being a calcite poison rather than a magnesian-calcite building block. The level of supersaturation may also play a role here, as it has been shown that supersaturation control can influence the CaCO 3 polymorph formation (Ahn et al, 2015).…”
Section: Influence Of Reaction Volumementioning
confidence: 99%